2006
DOI: 10.1210/en.2006-0070
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones and Rexinoids Induce Peroxisome Proliferator-Activated Receptor-Coactivator (PGC)-1α Gene Transcription: An Autoregulatory Loop Controls PGC-1α Expression in Adipocytes via Peroxisome Proliferator-Activated Receptor-γ Coactivation

Abstract: Thiazolidinediones (TZDs) are insulin-sensitizing drugs currently used to treat type 2 diabetes. They are activators of peroxisome proliferator-activated receptor (PPAR)-gamma, and adipose tissue constitutes a major site for their biological effects. PPAR coactivator (PGC)-1alpha is a transcriptional coactivator of PPARgamma and other transcription factors. It is involved in the control of mitochondrial biogenesis, and its activity has been linked to insulin sensitization. Here we report that PGC-1alpha gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 40 publications
9
119
0
1
Order By: Relevance
“…Indeed, the transcription of another MyoD target gene, UCP3, in which PGC-1␣ does not exert positive effects (11), is repressed by SIRT1. Moreover, the PGC-1␣-positive autoregulation of its own gene promoter has been previously reported and shown to be mediated by PPARs (25,26) or the myogenic factor MEF2C (5, 6), as also found in the present study. In light of the present findings, it could be hypothesized that other muscle genes that are targets of positive activation by MyoD and PGC-1␣ could be positively regulated by SIRT1.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the transcription of another MyoD target gene, UCP3, in which PGC-1␣ does not exert positive effects (11), is repressed by SIRT1. Moreover, the PGC-1␣-positive autoregulation of its own gene promoter has been previously reported and shown to be mediated by PPARs (25,26) or the myogenic factor MEF2C (5, 6), as also found in the present study. In light of the present findings, it could be hypothesized that other muscle genes that are targets of positive activation by MyoD and PGC-1␣ could be positively regulated by SIRT1.…”
Section: Discussionsupporting
confidence: 89%
“…Here, we do not provide an explanation about how palmitate-mediated NF-B activation results in PGC-1␣ downregulation, but several mechanisms could be involved. Interestingly, while this study was under evaluation, Hondares et al (46) reported the presence of a PPAR␥ response element in the promoter of the PGC-1␣ gene. Since MEK activation decreases PPAR␥ activity by phosphorylating this nuclear receptor and/or by interfering its transactivation activity (47), this provides a potential mechanism for the MEKmediated downregulation of PGC-1␣ after palmitate exposure.…”
Section: Diabetes Vol 55 October 2006mentioning
confidence: 85%
“…Specifically, Pgc-1α is phosphorylated and thereby activated by p38 mitogenactivated protein kinase (MAPK) in response to sympathetic stimulation 102,103 . Activated Pgc-1α regulates the expression of thermogenic genes through its interactions with Ppar-γ, Ppar-α, thyroid receptor and other factors 96,104,105 , although a detailed mechanism to account for its selective effects at brown fat-specific genes is lacking. Pgc1a transcription also increases in response to β-adrenergic agonists through increases in the function of activating transcription factor-2 (Atf2) 102 .…”
Section: Sympathetic Nerve Control Of Brown and Beige Fatmentioning
confidence: 99%